Our iceberg is melting : changing and succeeding under any condtions. - Kotter, John P., 1947-; Rathgeber, Holger, ....- (New York : St. Martin's, 2006)
In this business management fable, one penguin notices something problem that could become a big problem for the whole colony, but the other penguins don't want to listen, so he must convince and enlist the help of others to get something done. Most of the denizens of the Antarctic penguin colony sneer at Fred, the quiet but observant scout who detects worrying signs that their home, an iceberg, is melting. Fred must cleverly convince and enlist key players, such as Louis, the head penguin; Alice, the number two bird; the intractable NoNo the weather expert; and a passle of school-age penguins if he is to save the colony. Their delightfully told journey illuminates in an unforgettable way how to manage the necessary change that surrounds us all. Simple explanatory material following the fable enhances the lasting value of these lessons. 'Our Iceberg Is Melting' is at once charming, accessible and profound; a treat for virtually any reader.
Keywords: Veranderingsmanagement